The Japan self-defense forces law translation, history, and analysis - Eldridge, Robert D.; Musashi, Katsuhiro, 1961- (Cambridge Scholars Publishing, 2019)
This book is the first ever to examine the Japan Self-Defense Forces Law by providing an historical overview of its passage, changes, and function in Japanese defense policy since its passage in 1954. It is also the first to provide a full English translation of the Law, incorporating all of the more than 160 changes that have been adopted to it. This book will be of immense importance to students, scholars, practitioners, and officials working with or interested in Japan's ""military, "" a term that is recognized internationally but remains sensitive domestically.